Arte-educação: a ampliação da vida de sujeitos que fazem uso prejudicial de álcool e outras drogas. - Ana Carolina de Freitas Campos (2022)
This dissertation aimed to investigate the experience of art education within mental health services that take care of subjects who make harmful use of alcohol and other drugs. It is a mainly qualitative research in the exploratory modality, whose data were obtained from the narrative interviews with the art educators of mental health services-reference Centers in mental health for alcohol and drugs (CERSAM AD), Centers of Coexistence and Street Office - who provide care to subjects who make harmful use of alcohol and drugs. The dissertation was developed in the Professional Masters Program of the Universidade Federal de Minas Gerais, health promotion and violence prevention, based on the experiences and concerns arising from care in two mental health services. With this work, it’s intended to discuss the problems between the relationship of drug use and the criminalization of this practice, with prohibitionism, abstinence and also the incarceration of the poor, peripheral and black population, dealing as a police issue a public health issue. In addition, it reflects on the mental health policy with a general overview in Brazil and how services for people who use alcohol and drugs have been organized in the city of Belo Horizonte. Regarding the insertion of art education in mental health services, there is a great advance in the construction of healthcare, with practices built collectively with the subject, respecting the subjectivity of each one and proposing a new way to build a mediation between the real and the subjective field. Having a network that values the insertion of art education in health spaces is to affirm a commitment to public health built at many hands, denying the medical-centered logic and promoting listening and welcoming in various artistic languages.